Chemical Reporters for Exploring Microbiology and Microbiota Mechanisms. (27th December 2019) - Zhang, Zhenrun J.; Wang, Yen‐Chih; Yang, Xinglin; Hang, Howard C.
Abstract: The advances made in bioorthogonal chemistry and the development of chemical reporters have afforded new strategies to explore the targets and functions of specific metabolites in biology. These metabolite chemical reporters have been applied to diverse classes of bacteria including Gram‐negative, Gram‐positive, mycobacteria, and more complex microbiota communities. Herein we summarize the development and application of metabolite chemical reporters to study fundamental pathways in bacteria as well as microbiota mechanisms in health and disease. Abstract : New chemical tools : Advances in bioorthogonal chemical reporters have afforded new tools to explore the targets and functions of specific metabolites in diverse microbes. Here we summarize the development and application of metabolite chemical reporters to study fundamental pathways in bacteria as well as microbiota mechanisms in health and disease.